Efektivitas Pembuktian Mengenai TPPU Ditinjau Dari UU No. 8 Tahun 2010 Tentang TPPU - Pangaribuan, Yosep Martua Ganda; Marihot Marpaung, Sandro; Ferdiansyah, Reza (Universitas Ekasakti, 2023)
Corruption and money laundering cases, or Money Laundering Crimes (TPPU), have had significant negative impacts and incurred substantial losses for the country, reaching 138.39 trillion Indonesian Rupiahs from 2012 to 2022. In the efforts to address and uncover corruption and money laundering cases, Law No. 8 of 2010 concerning money laundering serves as the legal foundation for handling corruption cases. One of the processes stipulated in this legislation is the process of proving money laundering and corruption offenses. The evidentiary process plays a crucial role, where the search for evidence in corruption and money laundering cases forms the basis for court proceedings to assess whether the defendants or potential suspects in corruption cases have indeed committed money laundering and corruption offenses. However, the evidentiary process poses challenges due to numerous obstacles, especially when corrupt funds are transferred abroad. Researchers employed a normative juridical research method, utilizing descriptive analysis to assess the effectiveness of proving money laundering according to Law No. 8 of 2010. Based on the research conducted by the researchers, it was found that there are advantages in the law, such as facilitating investigators in obtaining banking data and sharing responsibilities with the Financial Transaction Reports and Analysis Center (PPATK) for analyzing the evidence. However, from a weakness perspective, the law has not provided investigators with the flexibility to seek evidence abroad and remains susceptible to threats